Acehnese Traditional Clothing Recognition Prototype System Design Based On Augmented Reality - Chicha Rizka Gunawan; Nurdin Nurdin; Fajriana Fajriana (International Journal of Engineering, Science and Information Technology, 2022)
Acehnese traditional clothing is one of the cultural heritages in Indonesia. In today's modern era, the problem faced is the lack of media to introduce cultural heritage in Aceh. Therefore, a media was formed that could introduce Aceh's traditional clothing, namely Southeast Aceh. The press utilizes Augmented Reality (AR) technology so that users can add virtual objects to the natural environment that are easy to use. In this study, a system design using Unified Modeling Language (UML) diagrams has been carried out, including use case diagrams, activity diagrams, and sequence diagrams. This system is built using the C++ language using the Unity application and the vuforiaSDK platform. Then the test results were obtained on the Southeast Aceh traditional clothing recognition application. Namely, the minimum distance that can display 3d objects is a distance of 5 cm, and the maximum distance that can be detected is 80 cm. Based on the test results in the distance test table, the best distance obtained, which results in the detection of markers that are still clear and bright, is at a distance between 5 cm to 70 cm. Meanwhile, at a distance of more than 80 cm, the marker cannot detect markers to display 3D objects because the distance between the camera and the marker is too far. Likewise, with the angular slope, the minimum angle of inclination detected is an angle of 0°, while the maximum angle of inclination detected is an angle of 75°. Based on the test results on the angle slope table, the best angle is obtained, which results in detecting markers that are still clear and bright at a distance between 0-60°. After that, testing is also carried out based on the lighting, where if the light is too bright or too dark, the camera cannot detect the marker.